Multikulturalisme Sebagai Identitas Kolektif, Kebijakan Politik dan Realitas Sosial - Setyaningrum, Arie (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2003)
The article offers an elaborate discussion on multiculturalism as collective identity, state (or public) policy and social fact. As a collective identity, multiculturalism implicates to diversity in cultural practices and how this cultural construct contribute to social and political process which in turn affect state policy formulation. As a policy, multiculturalism is a form of protectionist policy to maintain diversity in collective identity within a nation-state. As a social fact, multiculturalism is adoption of cultural and social diversity in day to day life. The article endeavors further chances of multiculturalism as an ideology becoming a national identity within the sphere of state policy. However, practices of multicultural policies, as argued here, are often disguised by a form of cultural hegemony as there are discriminatory political practices toward certain ethnic groups.